Circular Natural Geoforms, Sierras Pampeanas, Argentina - Gutierrez, Adolfo Antonio (2017)
We describe two circular morphological features representing depressed areas. This preliminary work is based on visual interpretations from Landsat ETM satellite images and SRTM Radar scans. The two geoforms are located at the north of the Sierras Pampeanas in Argentina. The La Ciénaga circular indentation is 15 km in diameter and Las Cejas is 34 km in diameter. Until now rings of these characteristics, magnitudes and diameters are unknown and unheard of in Argentina.